Intravitreal injection of fibrillin 2 (Fbn2) recombinant protein for therapy of retinopathy in a retina-specific Fbn2 knock-down mouse model - Zhang, Rui Xue; Wen, Ying; Guo, Da Dong; Xu, Fu Ru; Wang, Gui Min; Wang, Xing Rong; Shi, Yong Wei; Ding, Jie; Jiang, Qian; Jiang, Wen Jun; Jonas, Jost B.; Bi, Hong Sheng (Scientific reports, 2023)
Mutations in the extracellular matrix gene Fibrillin-2 (FBN2) are related to genetic macular degenerative disorders including age-related macular degeneration (AMD) and early-onset macular degeneration (EOMD). It was reported that the retinal protein expression of FBN2 was reduced in patients with AMD and EOMD. The effect of exogenously supplied fbn2 recombinant protein on fbn2-deficiency-related retinopathy was not known. Here we investigated the efficacy and molecular mechanism of intravitreally applied fibrin-2 recombinant protein in mice with fbn2-deficient retinopathy. The experimental study included groups (all n = 9) of adult C57BL/6J male mice which underwent no intervention, intravitreal injection of adeno-associated virus (AAV) empty vector or intravitreal injection of AAV-sh-fbn2 (adeno-associated virus for expressing short hairpin RNA for fibrillin-2) followed by three intravitreal injections of fbn2 recombinant protein, given in intervals of 8 days in doses of 0.30 μg, 0.75 μg, 1.50 μg, and 3.00 μg, respectively. Eyes with intravitreally applied AAV-sh-fbn2 as compared to eyes with injection of AAV-empty vector or developed an exudative retinopathy with involvement of the deep retinal layers, reduction in axial length and reduction in ERG amplitudes. After additional and repeated application of fbn2 recombinant protein, the retinopathy improved with an increase in retinal thickness and ERG amplitude, the mRNA and protein expression of transforming growth factor-beta (TGF-β1) and TGF-β binding protein (LTBP-1) increased, and axial length elongated, with the difference most marked for the dose of 0.75 μg of fbn2 recombinant protein. The observations suggest that intravitreally applied fbn2 recombinant protein reversed the retinopathy caused by an fbn2 knockdown.